Impact of low serum progesterone levels on the day of embryo transfer on pregnancy outcome: a prospective cohort study in artificial cycles with vaginal progesterone. Issue 3 (19th December 2020) - Labarta, Elena; Mariani, Giulia; Paolelli, Stefania; Rodriguez-Varela, Cristina; Vidal, Carmina; Giles, Juan; Bellver, José; Cruz, Fabio; Marzal, Alicia; Celada, Paula; Olmo, Ines; Alamá, Pilar; et al.
Abstract: STUDY QUESTION: Is there a serum progesterone (P) threshold on the day of embryo transfer (ET) in artificial endometrium preparation cycles below which the chances of ongoing pregnancy are reduced? SUMMARY ANSWER: Serum P levels <8.8 ng/ml on the day of ET lower ongoing pregnancy rate (OPR) in both own or donated oocyte cycles. WHAT IS KNOWN ALREADY: We previously found that serum P levels <9.2 ng/ml on the day of ET significantly decrease OPR in a sample of 211 oocyte donation recipients. Here, we assessed whether these results are applicable to all infertile patients under an artificial endometrial preparation cycle, regardless of the oocyte origin. STUDY DESIGN, SIZE, DURATION: This prospective cohort study was performed between September 2017 and November 2018 and enrolled 1205 patients scheduled for ET after an artificial endometrial preparation cycle with estradiol valerate and micronized vaginal P (MVP, 400 mg twice daily). PARTICIPANTS/MATERIALS, SETTING, METHODS: Patients ≤50 years old with a triple-layer endometrium ≥6.5 mm underwent transfer of one or two blastocysts. A total of 1150 patients treated with own oocytes without preimplantation genetic testing for aneuploidies (PGT-A) (n = 184), own oocytes with PGT-A (n = 308) or donated oocytes (n = 658) were analyzed. The primary endpoint was the OPR beyond pregnancy week 12 based on serum P levels measured immediately before ET. MAIN RESULTS AND THE ROLE OF CHANCE: Women with serum P levels <8.8 ng/ml (30th percentile) had a significantly lower OPR (36.6% vs 54.4%) and live birth rate (35.5% vs 52.0%) than the rest of the patients. Multivariate logistic regression showed that serum P < 8.8 ng/ml was an independent factor influencing OPR in the overall population and in the three treatment groups. A significant negative correlation was observed between serum P levels and BMI, weight and time between the last P dose and blood tests and a positive correlation was found with age, height and number of days on HRT. Multivariate logistic regression showed that only body weight was an independent factor for presenting serum P levels <8.8 ng/ml. Obstetrical and perinatal outcomes did not differ in patients with ongoing pregnancy regardless of serum P levels being above/below 8.8 ng/ml. LIMITATIONS, REASONS FOR CAUTION: Only women with MVP were included. Extrapolation to other P administration forms needs to be validated. WIDER IMPLICATIONS OF THE FINDINGS: This study identified the threshold of serum P as 8.8 ng/ml on the day of ET for artificial endometrial preparation cycles necessary to optimize outcomes, in cycles with own or donated oocytes. One-third of patients receiving MVP show inadequate levels of serum P that, in turn, impact the success of the ART cycle. Monitoring P levels in the mid-luteal phase is recommended when using MVP to adjust the doses according to the needs of the patient. STUDY FUNDING/COMPETING INTEREST(S): None. TRIAL REGISTRATION NUMBER: NCT03272412.